Analisis Biaya Kehilangan (LOSS COST) DARI Produk Air Minum dalam Kemasan (AMDK) Menggunakan Metode Poka Yoke - Syarifuddin Syarifuddin; Diana Khairani Sofyan (Jurnal Optimalisasi, 2016)
Quality is a common cause is natural to unite the functions of the business. One of the tools for quality improvement is Poka Yoke method. Poka Yoke is a technique to overcome and avoid simple mistakes that caused by humans or workers at the workplace. PT. Ima Montaz Sejahtera is one of the companies engaged in the production of bottled water (bottled water). Bottling line is a unit of production machinery which produces aqua medium 550 ml and large 1,500 ml consisting of three (3) main unit that is a bottle washing station, a water filling and a closure cap (capper). The problem that arises is the frequent occurrence of broken bottles and cups during the production of this may raise the cost of loss (loss cost) so as to reduce the profitability of the company. Based on these descriptions, it is necessary to observations oriented analysis (lost cost) in 550 ml of medium aqua products. Completion method to be used is the method of poka yoke. The results showed that the total lost cost products aqua medium 550 ml (September to August 2016) was 247,052,000, - where reject that occurred during the production process takes place is in the bottle and cap the cost of a bottle / unit amounted to Rp 1,200 and cap / unit Rp 80.The cost of damages from defective products is Rp 42,330,000, - with the cost of damages from defective cup is Rp 3,757,920, - bringing the total loss of Rp 46,087,920, -. In addition, the problem often occurs in capper unit wherein the corrective actions taken by the operator resulting in productivity stalled, problems that often occur is head capper unstable. The analysis showed that the largest percentage of the causes of errors often occur on the head capper unstable, operator of the less scrupulous and not focused when the production takes place, method of adjustment the capper unit that is not accurate and does not exactly head and chief bottle when fitting lid and the Inverter on a different machine.Keywords: Quality, Poka Yoke, Bottled water